P0057ADPKD: COMPLEX GENOTYPES MAY EXPLAIN SEVERE PHENOTYPE AND INTRAFAMILIAL PHENOTYPIC VARIABILITY. (6th June 2020) - Izzi, Claudia; Delbarba, Elisa; Econimo, Laura; Dordoni, Chiara; Savoldi, Gianfranco; Mazza, Cinzia; Dallera, Nadia; Scolari, Francesco
Abstract: Background and Aims: Discordant affected relative-pairs are seen in ∼10% of families with Autosomal Dominant Polycystic Kidney Disease (ADPKD); <1% of patients exhibit very early onset (VEO) disease. Complex genotypes may result in renal disease variability beyond that predicted by the sole effect of a single PKD mutant allele, leading to the discovery of biallelic or digenic disease. Here we illustrate such complexity in 6 ADPKD pedigrees. Method: Among our single-center ADPKD cohort (186 index patients), we selected pedigrees (P) in which marked familial phenotypic variability or severe and early onset disease was investigated by NGS and MLPA analysis of PKD1 and PKD2 genes and NGS analysis of other cystogenes. Segregation analysis by Sanger sequencing of PKD variants was performed in available affected and unaffected family members. Results: In P1 and P2, the index cases (IC), presented with very early onset (VEO) disease characterized by prenatal/neonatal enlarged and hyperechogenic kidneys mimicking autosomal recessive polycystic kidney disease (ARPKD). In P1, with neonatal onset, the ADPKD affected father transmitted a PKD1 PT variant p.Gln4231*, whereas the mother, without renal cystic phenotype, transmitted a PKD1 hypomorphic variant p.Asp1332Asn. In P2, the ADPKD-PKD2 mother's pregnancy was complicated by Potter sequence. Parent's PKHD1 gene analysis was negative. Two missense NT variants in PKD1/PKD2 genes were detected in the healthy father, respectively p.Gly1944Arg and p.Thr203Ile. Therefore, a complex PKD inheritance was supposed in the fetus. Fetus DNA was not available. In P3 early onset (EO) ADPKD in two monozygous twins was underpinned by a PKD1 NT variant (p.Arg1951Gln) inherited by the ADPKD mild affected father and worsened by a de novo PKD1 truncating variant p.Arg2402*. In P4 and P5 a digenic ADPKD (PKD1 +PKD2 and PKD1 +PKHD1) was diagnosed in severe ADPKD IC. In P4 the two most severely affected siblings carried a PKD2 T variant (p.Ala365fs) and a PKD1 NT variant p-Cys259Tyr. In P5 the IC presented with EO ADPKD, a de novo splicing variant c.2097 + 5_+6insT in PKD1 gene was discovered but the phenotype was probably worsened by the presence of biallelic variant in a second cystogene PKHD1: one paternally inherited: p.Gly1712Arg and one maternally inherited: p.Asp3088Asn . Elderly parents in P6 had mild ADPKD with bilateral few kidney cysts and preserved eGFR, whereas IC showed moderate/severe CKD due to ADPKD biallelic variants. The IC carried a homozygous PKD1 NT variant (p.Arg4154Cys): each mutant allele inherited from the mild ADPKD affected parents. Conclusion: Our study illustrates the genetic complexity in an otherwise "simple" Mendelian disorder, providing insights into the genetic basis of severity of ADPKD cases and into ADPKD intrafamilial disease variability. In our pedigree all cases with more severe clinical picture in the family presented at least two PKD variants. In P5 we found for the first time an EO ADPKD due to both PKD1 and PKHD1 variants. PKD1 and PKD2 sequence analysis together with cystic kidney disease gene panel analysis is recommended in those patients with discordant phenotype compared to family members. Molecular study of PKD patients is expected to be a good prognostic tool together with clinical and renal imaging data to better manage disease therapy, follow-up and reproductive issues.